REPRESENTASI PEREMPUAN DI PARLEMEN: STUDI PERBANDINGAN KEBERHASILAN KUOTA GENDER DI INDONESIA DAN SWEDIA - Hasanah, Rizka Luluatul; Zalvadhia, Nabila Kheisya; Mulyady, Santi; Nurdin, Nurdin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Women's representation in parliament is a key indicator in assessing the quality of democracy and gender equality in a country. This study compares the effectiveness of gender quota policies between Indonesia and Sweden to identify the factors contributing to their success or failure. Indonesia has formally implemented a 30% gender quota since 2004, yet its enforcement remains largely administrative and has not led to a significant increase in either the quantity or quality of female legislators. In contrast, Sweden has achieved nearly 50% female representation in parliament without a formal quota law, relying instead on voluntary political party commitments, a closed-list proportional electoral system, and an egalitarian political culture. This research employs a comparative qualitative approach using literature review as the primary data source. Findings indicate that the success of women’s political representation is not solely determined by legal quotas but is strongly influenced by structural party commitment, cultural support, and internal mechanisms such as the zipper system. The study recommends electoral system reform, capacity building for female politicians, and a cultural shift in political paradigms in Indonesia to ensure that gender quotas function as substantive affirmative action rather than symbolic compliance.